(untitled) (Revista Argentina de Cirugía, 2025)
Background: The treatment of W1 (1-4 cm) midline defects (M1-M5) admits various strategies, depending on the presence or absence of diastasis recti abdominis. Objective: The aim of this study was to compare the results of the ventral transabdominal peritoneal (TAPP) approach using traditional laparoscopic instruments (TVT) with mini-ventral TAPP (MVT) in terms of feasibility and safety. Material and methods: We conducted a prospective, experimental and randomized study with data collection and review of medical records from January 2021 to December 2023. Results: A total of 102 patients underwent hernia repair using the TVT (n = 51; 50%) and MVT (n = 51; 50%) techniques. The proportion of women was 54.90% in TVT group and 68.62% in MVT technique, with a mean age of 48.47 years. The percentage of patients with overweight was 72.54% in the TVT group and 45.09% in the MVT group and with grade I obesity in 27.45% and 54.90%, respectively. Primary M3-W1 hernias were more common in both groups (70.58% in TVT and 76.47% in MVT). Likewise, primary hernias were more common in TVT (62.74%) than in MVT (43.13%). There were no significant differences in length of hospital stay, intraoperative and postoperative complications, pain, recurrence and satisfaction in both groups. Conclusion: Both techniques proved to be safe and effective for the minimally invasive treatment of W1 midline hernias not associated with diastasis recti abdominis, confirming previous research in TVT.